Kansas meat marketing innovations - Jensen, F.E.; Erickson, D.B.; Trieb, S.E.; Tuma, H.J. (Kansas State University. Agricultural Experiment Station, 2011)
The U.S. system of producing, marketing, and distributing farm products has been heralded as the world’s most efficient, with lower distribution costs than any other nation. Research continues to improve marketing through new methods and technology. Central cryogenic-frozen meat packaging is an example.
Keywords: Beef; Marketing; Frozen meat; Tenderness